Phenolic Extract from Moringa oleifera Leaves Inhibits Key Enzymes Linked to Erectile Dysfunction and Oxidative Stress in Rats' Penile Tissues - Oboh, Ganiyu (Biochem Res Int, 2015)
This study was designed to determine the antioxidant properties and inhibitory effects of extract from Moringa oleifera leaves on angiotensin-I-converting enzyme (ACE) and arginase activities in vitro. The extract was prepared and phenolic (total phenols and flavonoid) contents, radical (nitric oxide (NO), hydroxyl (OH)) scavenging abilities, and Fe(2+)-chelating ability were assessed. Characterization of the phenolic constituents was done via high performance liquid chromatography-diode array detection (HPLC-DAD) analysis. Furthermore, the effects of the extract on Fe(2+)-induced MDA production in rats' penile tissue homogenate as well as its action on ACE and arginase activities were also determined. The extract scavenged NO(∗), OH(∗), chelated Fe(2+), and inhibited MDA production in a dose-dependent pattern with IC(50) values of 1.36, 0.52, and 0.38 mg/mL and 194.23 µg/mL, respectively. Gallic acid, chlorogenic acid, quercetin, and kaempferol were the most abundant phenolic compounds identified in the leaf extract. The extract also inhibited ACE and arginase activities in a dose-dependent pattern and their IC(50) values were 303.03 and 159.59 µg/mL, respectively. The phenolic contents, inhibition of ACE, arginase, and Fe(2+)-induced MDA production, and radical (OH(∗), NO(∗)) scavenging and Fe(2+)-chelating abilities could be some of the possible mechanisms by which M. oleifera leaves could be used in the treatment and/or management of erectile dysfunction.